NILAI KETAKTERATURAN TOTAL SISI DARI GRAF TANGGA PERMATA - Hanani, Hilmiyah; Slamin, S; Dafik, D (KadikmA, 2014)
Abstract. Let graph G = (V,E) has V vertices and E edges. For every two different edges of graph G has total irregularity strength labelling ofG ifÏt(e) â  Ït(f) where graph G = (V,E) has V vertices and E edges. The weight edge ofxy of a graph G is ð(xy) =ðx) +ðxy) + ðy) where ðx) is the label vertex x and ðy) is the label vertex y and ðxy) is the label edge of the xy. The minimum value on the biggest labels make a graph G, has irregular labeling which is defined as total edge irregularity strength and denoted by tes(G). In this article, The total edge irregularity strength of diamond ladder graph and the union of diamond ladder graphs (isomorphic) are determined. The diamond ladder graph, denoted by Dln, is a graph consisting ofn diamond (n â¥2) . Key Words : Total edge irregularity strength, Diamond Ladder Graph (Dln)